Clinical effectiveness of bidirectional fecal microbiota transfer in the treatment of recurrent Clostridioides difficile infections. Issue 6 (June 2021) - Bestfater, Christian; Vehreschild, Maria J.G.T.; Stallmach, Andreas; Tüffers, Kester; Erhardt, Andreas; Frank, Thorsten; Glück, Thomas; Goeser, Felix; Sellge, Gernot; Solbach, Philipp; Eisenlohr, Herbert; Storr, Martin; et al.
Abstract: Background: Fecal microbiota transfer (FMT) has become a standard of care in the prevention of multiple recurrent Clostridioides difficile (rCDI) infection. Aim: While primary cure rates range from 70–80% following a single treatment using monodirectional approaches, cure rates of combination treatment remain largely unknown. Methods: In a retrospective case-control study, outcomes following simultaneous bidirectional FMT (bFMT) with combined endoscopic application into the upper and lower gastrointestinal tract, compared to standard routes of application (endoscopy via upper or lower gastrointestinal tract and oral capsules; abbreviated UGIT, LGIT and CAP) on day 30 and 90 after FMT were assessed. Statistical matching partners were identified using number of recurrences (<3; ≥3), age and gender. Results: Primary cure rates at D30 and D90 for bFMT were 100% ( p =.001). The matched control groups showed cure rates of 81.3% for LGIT ( p =.010), 62.5% for UGIT ( p =.000) and 78.1% for CAP ( p =.005) on D30 and 81.3% for LGIT ( p =.010), 59.4% for UGIT ( p =.000) and 71.9% for CAP ( p =.001) on D90. Conclusion: In our analysis, bFMT on the same day significantly increased primary cure rate at D30 and D90. These data require prospective confirmation but suggest that route of application may play a significant role in optimizing patient outcomes. ClinicalTrials.gov no: NCT02681068